Prospek Industri Garam di Provinsi Maluku Berdasarkan Informasi Iklim - Trisna Sary Lewaru; Syarifuddin Syarifuddin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
This study aims to analyze the prospects of salt industries in Maluku Province based on climate information. The method used in this study is qualitative with a descriptive approach that uses meteorological time series data obtained from the BPS-Statistics Indonesia of Maluku Province. The data collected is the amount of rainfall, number of rainy days, and temperature in 2018. The analysis results conclude that Maluku Province has prospects for developing salt industries. Based on the climate information, the most appropriate locations for the industry establishment are Saumlaki, Geser, and Namlea, and the recommended period for production is July to November.